Ukraine : Technical Assistance Report-Strengthening Budget Formulation and Fiscal Risk Management. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance Paper on Ukraine discusses that implementing strategic planning and a medium-term budget framework (MTBF) is a core component of Ukraine's Public Financial Management (PFM) reform strategy. A pilot MTBF conducted in 2017 formed the basis for amendments to the Budget Code in December 2018, which firmly establish a MTBF as the basis for budget preparation. The amendments also establish a legal basis for related reforms, including regular spending reviews and monitoring and managing risks to public finances. The report also highlights that a central margin should also be established to accommodate budget volatility and meet the costs of genuinely urgent, unavoidable and unforeseeable expenditure pressures that may arise. In order to reinforce spending discipline, the margin should be tightly controlled, centrally managed and transparently reported. Strategic planning should also be improved to provide a stronger basis for integrated policymaking, strategizing, planning and budgeting. Creating a robust strategic planning system would assist in this regard.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet